FEATURES OF TRANSIT FROM POSTSOCIALISM - Іллєнко, Д.В. (The Journal of V.N. Karazin Kharkiv National University. Series "Issues of Political Science")
The article considers the notion of postsocialism, which brought together many approaches to determine the causes and future development in the former socialist countries. There analyzed the basic central approaches to the conceptualization of the socialist legacy. The causes and course of democratic transit, which took place in the years 1989-1991 in the post-Soviet countries differed greatly from democratization process that took place in Southern Europe and Latin America. Criticism arising from the use of these approaches in the postsocialist region is also considered in this article as well as new attempts conceptualization of democratization in postsocialist regions of Europe.